Analysis and design of online publice service - Abate, Yinagn (My University, 2018)
This research deals with the barriers of E-Government functioning in Ethiopia, The main goal of this research is to identify the problems associated with Passport application/registration and to provide an appropriate solutions. The research discusses the current situation concerning the E.-Government in Ethiopia and analyzes the extent of e-services coverage in the country. Once the drawbacks are found out, the author proposes the creation of online service portal. The creation of the portal will be based on the literature sources analysis, author 's personal experience and conducted sample surveys. In the practical part, a web application was created using HTML5, CSS3 and PHP. The application includes detailed information about the user (passport applicant), such as full name, date of birth, address and other attributes. This data should be uploaded to a SQL database, which will in turn transmit the information to the web application.
Analýza a návrh on-line veřejné služby
Keywords: analýza; E-Government v Addis Abebě v Etiopii; online služby; webové aplikace, e-služby; Analýza; návrh; on-line; veřejné; služby